A bio-sensing platform based on graphene quantum dots for label free electrochemical detection of progesterone. (2022) - Disha,; Kumari, Poonam; Nayak, Manoj K.; Kumar, Parveen
Highlights: The work employs the Glassy carbon electrodes modified with graphene quantum dots. Electrochemical detection of progesterone steroid hormone by Cyclic Voltammetry. Progesterone sensing with different concentrations using the functionalized electrodes. Abstract: The present study describes the development of graphene quantum dots (GQDs) based label-free immunosensor for sensing progesterone, a steroid hormone, using an electrochemical approach to monitor health issues and environmental contaminations. For this purpose, GQDs were synthesized by bottom-up approach and were deposited on glassy carbon substrate as a working electrode. The formation of GQDs was confirmed by UV–Vis, FTIR, RAMAN spectroscopy, and HR-TEM, and Cyclic Voltammetry was applied to investigate the electrochemical performance of the immunosensor. Further, the biosensor was optimized to detect progesterone at low concentrations. The proposed biosensor opens to be a promising platform for simplified and rapid steroid hormone analysis in biological applications and pharmaceutical formulations.